An assessment of atmospheric mercury in the Community Multiscale Air Quality (CMAQ) model at an urban site and a rural site in the Great Lakes Region of North America - T. Holloway; C. Voigt; J. Morton; S. N. Spak; A. P. Rutter; J. J. Schauer (Atmospheric Chemistry and Physics, 2012)
Quantitative analysis of three atmospheric mercury species – gaseous elemental mercury (Hg0), reactive gaseous mercury (RGHg) and particulate mercury (PHg) – has been limited to date by lack of ambient measurement data as well as by uncertainties in numerical models and emission inventories. This study employs the Community Multiscale Air Quality Model version 4.6 with mercury chemistry (CMAQ-Hg), to examine how local emissions, meteorology, atmospheric chemistry, and deposition affect mercury concentration and deposition the Great Lakes Region (GLR), and two sites in Wisconsin in particular: the rural Devil's Lake site and the urban Milwaukee site. Ambient mercury exhibits significant biases at both sites. Hg0 is too low in CMAQ-Hg, with the model showing a 6% low bias at the rural site and 36% low bias at the urban site. Reactive mercury (RHg = RGHg + PHg) is over-predicted by the model, with annual average biases >250%. Performance metrics for RHg are much worse than for mercury wet deposition, ozone (O3), nitrogen dioxide (NO2), or sulfur dioxide (SO2). Sensitivity simulations to isolate background inflow from regional emissions suggests that oxidation of imported Hg0 dominates model estimates of RHg at the rural study site (91% of base case value), and contributes 55% to the RHg at the urban site (local emissions contribute 45%).